The association between sodium–glucose cotransporter 2 inhibitors and contrast-associated acute kidney injury in patients with type 2 diabetes undergoing angiography: a propensity-matched study - Yang, Hao; Yang, Lili; Jardine, Meg J.; Arnott, Clare; Neuen, Brendon L.; Xu, Kexi; Zhao, Xiaohui; Qian, Dehui; Cui, Bin; Qiu, Youzhu; Huang, Yuli; Yu, Jie; et al. (European journal of medical research, 2024)
Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have been proven to prevent decline in kidney function and failure. Whether SGLT2i affect the risk of contrast-associated acute kidney injury (CA-AKI) remains uncertain. Use of SGLT2i was assessed in consecutive diabetics undergoing coronary angiography (CA) or percutaneous coronary intervention (PCI) from January 2020 to May 2023 at a tertiary hospital in Chongqing, China. Propensity-matched analysis was used to adjust for baseline variables. CA-AKI was defined by the Acute Kidney Injury Network (AKIN) as creatinine increase ≥ 0.3 mg/dl (26.4 μmol/l), or a percentage increase in the serum creatinine level of ≥ 50%. A total of 604 new users of SGLT2i, and 298 chronic users of SGLT2i were matched with non-users. New use of SGLT2i was not associated with an increased incidence of AKIN-defined CA-AKI (OR 1.60; 95% CI 0.97-2.63; p = 0.065), in-hospital new-onset dialysis (OR 0.50; 95% CI 0.09-2.73; p = 0.422), or death (OR 0.55; 95% CI 0.18-1.66; p = 0.289). However, it was associated with a minor (> 25%) creatinine elevation (OR 1.55; 95% CI 1.04-2.30; p = 0.030), a 0.3 mg/dl increase in creatinine (OR 1.66; 95% CI 1.01-2.75; p = 0.048), and CMSC-defined CA-AKI (OR 1.51; 95% CI 1.02-2.24; p = 0.039). By 90 days, there was no evidence creatinine elevation differed between the two groups (p = 0.590). Chronic use of SGLT2i was not associated with AKIN-defined CA-AKI (OR, 0.92; 95% CI 0.41-2.05; p = 0.838). New use of SGLT2i during CA or PCI was not associated with an AKIN-defined CA-AKI, and it did not translate into new-onset dialysis or death during hospital stay. Chronic usage of SGLT2i did not affect creatinine. Further randomized clinical trials are warranted to confirm this finding.